2018
DOI: 10.3892/mco.2018.1671
|View full text |Cite
|
Sign up to set email alerts
|

Geriatric nutritional risk index predicts surgical site infection after pancreaticoduodenectomy

Abstract: Surgical site infections (SSIs) are a well-known potential complication of surgery. They are assocaited with preoperative malnutrition and lead to increased medical costs and longer hospital stays. Therefore, surgeons should appropriately identify patients who are at a high risk. The geriatric nutritional risk index (GNRI) is a tool, increasingly utilized to assess the degree of malnutrition, particularly in elderly patients. Therefore, the present study attempted to validate whether GNRI could predict the ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 28 publications
0
22
0
1
Order By: Relevance
“…The GNRI based on the two variables was developed to evaluate malnutrition and related morbidity and mortality in hospitalized elderly patients [6]. The GNRI has been reported to be a useful tool to predict surgical site infection after pancreaticoduodenectomy [15], nutritional status and clinical outcomes in peritoneal dialysis patients [16], and clinical outcomes in patients with pyogenic liver abscess [17]. On the other hand, the CONUT based on the three variables was developed to detect malnutrition and assess nutritional status in hospitalized patients [7].…”
Section: Discussionmentioning
confidence: 99%
“…The GNRI based on the two variables was developed to evaluate malnutrition and related morbidity and mortality in hospitalized elderly patients [6]. The GNRI has been reported to be a useful tool to predict surgical site infection after pancreaticoduodenectomy [15], nutritional status and clinical outcomes in peritoneal dialysis patients [16], and clinical outcomes in patients with pyogenic liver abscess [17]. On the other hand, the CONUT based on the three variables was developed to detect malnutrition and assess nutritional status in hospitalized patients [7].…”
Section: Discussionmentioning
confidence: 99%
“…related morbidity and mortality in elderly patients (6). Our previous study showed that a low GNRI was associated with wound infections and POPF in patients who undergo PD (15). Therefore, we hypothesized that GNRI could be predictive of POPF following DP.…”
Section: Discussionmentioning
confidence: 93%
“…Among them, we focused on GNRI, which includes albumin and BMI, primarily because of availability of the required parameters and lack of invasiveness. Until now, it had been reported that lower GNRI was associated with increased risk of surgical site infections in patients following PD [ 11 ], and POPF in patients with distal pancreatectomy at a different hospital [ 22 ]. In detail, a lower GNRI value was strongly associated with a higher risk of surgical site infections, supporting the use of nutritional assessment prior to an elective surgical procedure.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Wang et al showed that GNRI could be used to risk stratify elderly patients who underwent radiotherapy or definitive concurrent chemoradiotherapy [ 27 ]. In addition, our previous report revealed that GNRI has been identified as a risk factor for SSIs in patients after PD [ 11 ]. Moreover, Kushiyama et al showed that GNRI is useful marker in predicting postoperative complications for elderly patients after gastrectomy [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation